Foodomics: a new perspective on gut probiotics nutrition and health research - He, Mengxue; Tan, Chin Ping; Liu, Yuanfa; Xu, Yong Jiang (Elsevier, 2021)
Probiotics that are living microorganisms, can produce health benefits to the host when administered in sufficient amounts. Various high throughput and sensitivity technology have been employed in the research of gut probiotics, since their extremely sophisticated action mechanism. Foodomics that integrated multiple omics technologies has been widely used for gut probiotics study. This article reviews the advanced technologies in foodomics and gives a comprehensive, critical overview of current state of the art, future challenges and trends of foodomics in gut probiotics nutrition and health investigation.